Effects of carbon nanodot fractionation on the performance of sensitized mesoporous titania based photovoltaic devices. Issue 22 (27th May 2022) - Essner, Jeremy B.; Boogaart, Dustin J.; Baker, Sheila N.; Baker, Gary A.
Abstract : Ubiquitous carbon dot synthesis by-products generate photocurrent, impacting overall device performance, highlighting the urgency of enhanced scrutiny and more rigorous purification protocols and, in many cases, reevaluation of previous results. Abstract : Fluorescent carbon dots hold particular appeal owing to their facile and sustainable preparation, biocompatibility, and outwardly superlative optical characteristics. However, growing evidence points to the fact that, in many cases, fluorescent features originate predominantly from molecular organic by-products rather than the presumed nanocarbons. To confront this exigent matter, in this work, carbon dots were prepared following four representative bottom-up syntheses: pyrolysis of citric acid in aqueous ammonia; solvothermal treatment of ethanolic l -arginine; microwave irradiation of aqueous citric acid-urea; and solvothermal decomposition of glutathione in formamide. The resulting crude "carbon dot" samples were fractionated using 50 kDa cutoff dialysis membranes and the resulting fractions ( i.e., as-synthesized, retentate, dialysate) employed as photosensitizers within mesoporous titania-based photovoltaic devices to systematically explore their relative performance in light-harvesting applications. Our results unequivocally demonstrate that reaction by-products ubiquitously generate photocurrent, making principal contributions to the observed device performance. These results draw further attention to the need for (i) closer scrutiny of carbon nanodot claims; (ii) widespread implementation of rigorous and uniform purification and validation protocols; and, (iii) revisitation of prior work, particularly in cases where exceptional or extraordinary claims have been made.